UPAYA MENINGKATKAN DISIPLIN GURU DALAM MENGAJAR PADA MASA PANDEMI COVID-19 MELALUI PEMBINAAN DI SLB MELATI RUMBAI KOTA PEKANBARU - Maidar (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
In terms of increasing the teacher's role in the teaching and learning process and students’ learning outcomes, the teacher is expected to be able to make an effective learning environment and will be able to manage the class. Teachers are professional educators with the main task of educating and evaluating students in the context of early childhood education through formal education, elementary, and secondary education level. Meanwhile, employees in education are part of education or community members who devote themselves and are appointed to support the implementation of education. Based on the information of Wiyatamandala, teacher discipline is defined as a mental attitude that contains a willingness to apply every applicable provision, rule, and norm in carrying out the duties and responsibilities. Based on the observations at the Special School of Melati Rumbai in Pekanbaru, it was found the phenomena that there were still many teachers who came late to school, there was still a lack of teacher discipline in teaching in the classroom, and teachers were often late for class. The purpose of the research in this article was to determine whether teacher discipline in teaching could be improved through coaching at SLB Melati Rumbai Pekanbaru or not. The subjects involved 26 teachers at the Special School of Melati Rumbai in Pekanbaru. Related to the description of the data and discussion, it was concluded that teacher discipline in teaching was obtained in the first cycle of 62% in the good category and in the second cycle increased to 89% in the good category. It means that coaching activities could improve teacher discipline in teaching at SLB Melati Rumbai Pekanbaru.